2020
DOI: 10.1038/s41467-020-16071-5
|View full text |Cite
|
Sign up to set email alerts
|

Iron-mediated organic matter decomposition in humid soils can counteract protection

Abstract: Soil organic matter (SOM) is correlated with reactive iron (Fe) in humid soils, but Fe also promotes SOM decomposition when oxygen (O 2) becomes limited. Here we quantify Femediated OM protection vs. decomposition by adding 13 C dissolved organic matter (DOM) and 57 Fe II to soil slurries incubated under static or fluctuating O 2. We find Fe uniformly protects OM only under static oxic conditions, and only when Fe and DOM are added together: de novo reactive Fe III phases suppress DOM and SOM mineralization by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
248
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 278 publications
(265 citation statements)
references
References 80 publications
(220 reference statements)
13
248
4
Order By: Relevance
“…This may be linked to the different oxidation levels of Fe. At higher precipitation levels, Fe oxides can be reduced, resulting in a release of associated SOC to the aqueous phase (Berhe et al 2012;Chen et al 2020;Thompson et al 2011). This mechanism is probably responsible for the low correlation between SOC and high Feox concentrations in our data (Figure 5e), pointing to the fact that Feox can act as pedogenic threshold, depending on its oxidation level in the soil system.…”
Section: Oxalate Al and Fementioning
confidence: 76%
“…This may be linked to the different oxidation levels of Fe. At higher precipitation levels, Fe oxides can be reduced, resulting in a release of associated SOC to the aqueous phase (Berhe et al 2012;Chen et al 2020;Thompson et al 2011). This mechanism is probably responsible for the low correlation between SOC and high Feox concentrations in our data (Figure 5e), pointing to the fact that Feox can act as pedogenic threshold, depending on its oxidation level in the soil system.…”
Section: Oxalate Al and Fementioning
confidence: 76%
“…They found that on average 15% of organic C in the studied cores is directly bound to reactive Fe, corroborating the findings in estuarine and marine sediments. These results are counter-intuitive because ligand exchange was shown to be suppressed by SO 4 2− (Table 1) [40,41], which is abundant in seawater (0.03 M), and because Fe can undergo reductive dissolution as Fe(II) in reducing environments, leading to the disruption of the OM-Fe interactions [25,26]. Compared to marine sediments, mangrove soils are a much more redox dynamic environment, thus the interactions of OM and Fe at redox interfaces may be more important than in marine sediments.…”
Section: Mineral Soils: Interactions With Soil Minerals or Metalsmentioning
confidence: 99%
“…Moreover, the decomposition rate of mangrove litter and roots varies considerably within and between mangrove forests [11,20,21]. Soils with more saturated conditions can have higher OM decomposition rates compared to drier conditions, for instance by enhanced leaching or through the release of physico-chemically protected OM due to metal reduction [22][23][24][25][26]. As such, the postulated low decomposition rate of mangrove soil C due to the suboxic condition may not be universal to all mangroves.…”
Section: Introductionmentioning
confidence: 99%
“…The alternate tested method of using wet samples has largely been avoided, with only a few studies (e.g. van Bodegom et al, 2003;Chen et al, 2020) reporting the use of a wet slurry sample in soils and none for sediments. Chen et al (2020) justify their use of slurries as being to "minimise the physical-protection mechanisms of aggregation", acknowledging that drying methods are likely to result in superficial particle protection.…”
Section: Freeze Drying Of Samples As a Limiting Factor On Fe Reductionmentioning
confidence: 99%
“…Finally, sample preparation methods were examined since the commonly applied method of freeze drying is thought to cause particle aggregation, which may artificially shield Fe phases from reduction. The alternative approach of using a sediment slurry has been applied to soils (Chen et al, 2020) but has not been investigated in the context of marine sediments.…”
Section: Introductionmentioning
confidence: 99%